Draft of a letter - Longenbach, James (Phoenix poets., 2007)
From Second Draft:. What other people learn. From birth, . Betrayal, . I learned late. My soul perched. On an olive branch. Combing itself, . Waving its plumes. I said. Being mortal, . I aspire to. Mortal things. I need you, . Said my soul, . If you?re telling the truth. Draft of a Letter is a book about belief?not belief in the unknowable but belief in what seems bewilderingly plain. Pondering the bodies we inhabit, the words we speak, these poems discover infinitude in the most familiar places. The revelation is disorienting and, as a result, these poems talk to themselves, revise themselves, fash.